Magnetism of two-dimensional chromium tellurides - Yang, Jiefu (2023)
2D ferromagnets have garnered considerable attention for their potential applications in spintronics, magnonics, and spin-orbitronics. Chromium tellurides (CrxTey), in particular, have drawn interest due to their exceptional magnetic properties and diverse range of chemical stoichiometries, attributed to the phenomenon of chromium self-intercalation. To provide an in-depth understanding of this complex material class, this review first explains the origin of 2D magnetism using two well-known 2D ferromagnets, CrI3 and Fe3GeTe2, and compares the structures of CrTe2, Cr5Te8, Cr2Te3, and CrTe to clarify the self-intercalation phenomenon. In addition, it summarizes the growth conditions of CrxTey using the chemical vapor deposition approach as well as commonly practiced characterization techniques for 2D ferromagnetism. This review also compares ferromagnetic properties while analyzing how Cr intercalants affect the magnetic. Finally, it suggests that more attention should be focused on this material system to unlock its full practical and academic potential, and proposes directions for future research.